Prevalence of behavioral risk factors among Ukrainians during war amid existing stress factors - Olena Kolesnikova; Olena Vysotska; Anastasiia Radchenko; Olga Zaprovalna; Nataliya Emelyanova (Academia Medicine)
Background: Military conflicts and associated stress often lead to lifestyle changes. Unhealthy behaviors play a pivotal role in the development of cardiovascular risk factors and are potentially reversible. However, data on this topic remain scarce and outdated. Therefore, the objective of our study was to assess the prevalence of behavioral risk factors (BRFs) among Ukrainians, taking into account the presence of potential stress factors. Methods: From January to August 2023, we conducted a survey involving 196 Ukrainians. We used a proprietary questionnaire to determine their health status and evaluate behavioral, socio-economic, and cultural factors. Results: Sleep disturbances were reported by 72.4% of respondents, while 55.6% noted a reduction in physical activity. Dietary issues were reported by 34.7%, with 22.4% experiencing weight gain and 36.2% reporting weight loss. In addition, 13.3% and 16.8% indicated increased smoking and alcohol consumption, respectively. We provided an overview of the stress factors affecting these BRFs. Furthermore, we identified differences in the prevalence of BRFs based on indicators such as reduced quality of life, social maladjustment, work-related factors, and traumatic experiences. Finally, we offered recommendations for a screening strategy for BRFs. Conclusions: In wartime conditions, civilians often exhibit BRFs such as sleep disorders, dietary disturbances, decreased physical activity, increased smoking, and alcohol abuse. Specific stress factors contribute to the emergence and exacerbation of these behaviors. Screening programs should be developed with consideration of the identified stressors.